Unprecedented Electron‐Poor Octahedral Ta6 Clusters in a Solid‐State Compound: Synthesis, Characterisations and Theoretical Investigations of Cs2BaTa6Br15O3. Issue 38 (5th August 2013) - Demont, Antoine; Prestipino, Carmelo; Hernandez, Olivier; Elkaïm, Erik; Paofai, Serge; Naumov, Nikolaï; Fontaine, Bruno; Gautier, Régis; Cordier, Stéphane
Abstract The crystal structure of Cs2BaTa6Br15O3 has been elucidated by using synchrotron X‐ray powder diffraction and absorption experiments. It is built from edge‐bridged octahedral [(Ta6 <![CDATA[${{\rm Br}{{{\rm i}\hfill \atop 9\hfill}}}$]]> <inline-graphic xlink:href="ark:/27927/pgg37rmnpd0" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[${{\rm O}{{{\rm i}\hfill \atop 3\hfill}}}$]]> <inline-graphic xlink:href="ark:/27927/pgg37rmnpcf" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) <![CDATA[${{\rm Br}{{{\rm a}\hfill \atop 6\hfill}}}$]]> <inline-graphic xlink:href="ark:/27927/pgg37rmnpm9" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />]4− cluster units with a singular poor metallic electron (ME) count equal to thirteen. This leads to a paramagnetic behaviour related to one unpaired electron. The arrangement of the Ta6 clusters is similar to that of Cs2LaTa6Br15O3 exhibiting 14‐MEs per [(Ta6 <![CDATA[${{\rm Br}{{{\rm i}\hfill \atop 9\hfill}}}$]]> <inline-graphic xlink:href="ark:/27927/pgg37rmnphn" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[${{\rm O}{{{\rm i}\hfill \atop 3\hfill}}}$]]> <inline-graphic xlink:href="ark:/27927/pgg37rmnp6p" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) <![CDATA[${{\rm Br}{{{\rm a}\hfill \atop 6\hfill}}}$]]> <inline-graphic xlink:href="ark:/27927/pgg37rmnp8s" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />]5− motif. The poorer electron‐count cluster presents longer metal–metal distances as foreseen according to the electronic structure of edge‐bridged hexanuclear cluster. Density functional theory (DFT) calculations on molecular models were used to rationalise the structural properties of 13‐ and 14‐ME clusters. Periodic DFT calculations demonstrate that the electronic structure of these solid‐state compounds is related to those of the discrete octahedral units. Oxygen–barium interactions seem to prevent the geometry of the octahedral cluster to strongly distort, allowing stabilisation of this unprecedented electron‐poor Ta6 cluster in the solid state.